REVITALIZATION OF THE ORIGINAL CULTURE OF BONDOWOSO DISTRICT AS A CULTURAL HERITAGE: REVITALISASI TERHADAP BUDAYA ASLI DAERAH KABUPATEN BONDOWOSO SEBAGAI WARISAN BUDAYA - Deni Kurniawan Efendi; Bayu Septa Martaviano Triaiditya (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2020)
Revitalization research on culture in Indonesia still uses the publication method on social media. This study aims to recall the culture that exists in several areas, especially Bondowoso Regency itself, as well as to produce products and increase the knowledge of the community, youth and students about indigenous culture in Bondowoso Regency. The research was conducted with field observations, interviews with related agencies, cultural centers, cultural experts in Bondowoso Regency, the results of which can later be disseminated to all communities, youth and students to better understand and know about the indigenous culture of Bondowoso Regency itself.